Geliat agitasi gender dan anti pelecehan seksual: Kajian perspektif sosial profetik Kuntowijoyo - Perdana Putra Pangestu (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
Sexual harassment and violence seem taboo and have not been properly internalized in the social area of our society. The popularity of cases that seem to be constantly appearing in the eyes of the public has formed a massive collective agitation to crush the naughty sexual paradigm. The author is interested in studying how movements and counter-narratives are constructed to realize freedom and understanding related to sexual harassment. The author takes a qualitative approach through a literature review and existing phenomena. The description of the study will be obtained by optimizing the formulation of the interpretation of the topic surrounding the issue of sexual harassment. The interpretation and data elaboration were then analyzed using Kuntowijoyo's Social Prophetic theoretical line. This research concludes that various forms of agitation are exposed as exposures in building the value of humanization and liberation for all people fairly and safely.